Characterization of physical performance and change of direction deficit across age groups in young female volleyball players - Oliveira, J. P.; Marinho, D. A.; Jacinto, P.; Sampaio, T.; Morais, J. E. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Volleyball performance relies heavily on agility, strength, and the ability to change direction, yet there is limited research investigating these physical attributes across different age groups in youth volleyball players. The change of direction (COD) deficit - a metric that isolates directional efficiency by comparing agility to linear speed - may provide a more nuanced understanding of an athlete`s movement capabilities. The aim of this study was to investigate: (i) the differences in anthropometrics, lower limb strength/power, dynamic balance, linear sprint speed, and change of direction (COD) ability between young volleyball age groups; (ii) the effect of age on COD deficit in young volleyball players, and; (iii) the COD deficit predictors.